Ephrin Ligands and Eph Receptors Show Regionally Restricted Expression in the Developing Palate and Tongue - Xavier, Guilherme M.; Miletich, Isabelle; Cobourne, Martyn T. (Frontiers in Physiology, 2016)
The Eph family receptor-interacting (ephrin) ligands and erythropoietin-producing hepatocellular carcinoma (Eph) receptors constitute the largest known family of receptor tyrosine kinases. Ephrin ligands and their receptors form an important cell communication system with widespread roles in normal physiology and disease pathogenesis. In order to investigate potential roles of the ephrin-Eph system during palatogenesis and tongue development, we have characterized the cellular mRNA expression of family members EphrinA1-A3, EphA1–A8 and EphrinB2, EphB1, EphB4 during murine embryogenesis between embryonic day 13.5–16.5 using radioactive in situ hybridization. With the exception of EphA6 and ephrinA3, all genes were regionally expressed during the process of palatogenesis, with restricted and often overlapping domains. Transcripts were identified in the palate epithelium, localized at the tip of the palatal shelves, in the mesenchyme and also confined to the medial epithelium seam. Numerous Eph transcripts were also identified during tongue development. In particular, EphA1 and EphA2 demonstrated a highly restricted and specific expression in the tongue epithelium at all stages examined, whereas EphA3 was strongly expressed in the lateral tongue mesenchyme. These results suggest regulatory roles for ephrin-EphA signaling in development of the murine palate and tongue.